CONTRIBUTION OF AGRICULTURAL SECTOR AND ITS REFLECTION ON GDP IN INDIA - Theenathayalan, S.; Murugan, S. (International Journal of Psychosocial Rehabilitation, 2024)
This paper aims to analyse the relationship between the contribution of agricultural sector and the total GDP in India. Agricultural sectorin India is expected to generate better momentum in next few years due to increased investment in agricultural infrastructure. Increased agricultural output and productivity tend to contribute substantially to the overall economic prosperity of a nation which is predominantly agricultural and over-populated. Still agriculture in India is the backbone of the country and is regarded as the largest sector of the country’s economic activity. The regression result shows that one percent increase in agricultural GDP which leads to increases 1.79 per cent of total GDP. The R2 value is 0.95. It shows the present contributory position of Indian Agricultural sector. Above the all without Agricultural and Allied Activities no one can survive in the earth. In this relation Agricultural GDP has positive impact on not only in India’s GDP but also for the people who involved in industrial and service sector activities.